Development And Validation Of An Rp-Hplc Method For Quantitative Estimation Of Apixaban In Pharmaceutical Dosage Forms - Nagargoje, Sanjay S.; Hossain, Maruf; Salim, Meman Rahil; Nanda, Naimish; Borade, Amol Uttamrao; Vohra, Samriti; Chandna, Amit; Maurya, Uma Shanker (Journal of Neonatal Surgery, 2025)
A simple, precise, and accurate reverse-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated to measure Apixaban (APIX) in pharmaceutical formulations. Chromatographic separation was achieved using a C18 column, a mobile phase made up of acetonitrile and water in a 70:30 (v/v) ratio, a flow rate of 1.0 mL/min, and detection at 280 nm. In compliance with ICH guidelines, the procedure's linearity, precision, accuracy, selectivity, sensitivity, recovery, and robustness were all verified. Over the range of 5.0–40.5 µg/mL, APIX demonstrated strong linearity and a correlation coefficient (R2) of 0.9997. Intra-day and inter-day precision trials verified the approach's dependability, showing accuracy ranging from -1.89% to 2.67% with RSD values below 3%. Forced degradation studies indicated that APIX was stable under acidic and neutral conditions but degraded significantly under alkaline, thermal, and photolytic stress. When the technique was applied to commercially available tablet formulations, the average content was 9.19 ± 0.05 mg per tablet, with recovery rates ranging from 99.05% to 101.67%. The created technique indicates stability and is appropriate for regular quality control examinations of Apixaban in tablet dosage forms.